Kimmel on Climate: Disentangling the Emotional Ingredients of a Satirical Monologue. Issue 4 (August 2019) - Skurka, Chris; Niederdeppe, Jeff; Nabi, Robin
This study explored whether satire (an emotional blend of humor/indignation) can minimize the emotional tradeoffs researchers have documented for humorous appeals about climate change. Using a sample of U.S. young adults, we conducted a 2 (humor: present/absent) × 2 (indignation: present/absent) + 1 (control) experiment in which we manipulated a climate change segment from Jimmy Kimmel Live! Our evidence suggests that it is possible for a late-night host to affect young adults' climate change risk perception and behavioral intentions under certain conditions. Moderation analyses indicated that avoiding humor helped close the partisan gap in risk perception between Republicans and Democrats.